Synthesis and Biological Study of Some New Pyrrolidines - A.J. Al-Hamdany; A. Mustafa; M. Abdulrahman (College of Education for Pure Sciences, 2007)
ABSTRACT A series of Schiff bases N-Arylidene benzylamie (1-6) have been prepared, and through 1,3-anionic cycloaddition under strong basic conditions were added to benzoquinone to afford the fused new pyrrolidines (7-12). The spectroscopic methods were used to confirm the structures of the new products, as well as melting points. The suggested mechanisms of most of the reactions were investigated theoretically on the basis of the values of heat of formation and steric energy of the products. A preliminary biological activity on E. coli and Staph. aureus of the products had also been tested.